Penguatan Nilai Kearifan Lokal â€œPoda Na Limaâ€ Dalam Pembentukan Karakter Generasi-Z Desa Lintongnihuta Kecamatan Ronggurnihuta Kabupaten Samosir - Naibaho, Zanrison; Marlina, Murni Eva; Pasaribu, Payerli; Malau, Waston (Yayasan Daarul Huda Kruengmane, 2024)
Lintongnihuta Village, Ronggurnihuta District, Samosir Regency is a partner village that is the target audience for the Community Partnership Program with the activity of Implementing Local Wisdom Values